2017
DOI: 10.1111/ibi.12462
|View full text |Cite
|
Sign up to set email alerts
|

Comparative migration strategies of wild and captive‐bred Asian Houbara Chlamydotis macqueenii

Abstract: For migratory species, the success of population reintroduction or reinforcement through captive-bred released individuals depends on survivors undertaking appropriate migrations. We assess whether captive-bred Asian Houbara Chlamydotis macqueenii from a breeding programme established with locally sourced individuals and released into suitable habitat during spring or summer undertake similar migrations to those of wild birds. Using satellite telemetry, we compare the migrations of 29 captive-bred juveniles, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 40 publications
(88 reference statements)
1
38
0
2
Order By: Relevance
“…If a nest was not found after~30 min the tracking was stopped, to avoid keeping a female off her nest too long (data from nest cameras indicated that females take incubation breaks of~30 min; R. J. Burnside personal observation). For 27 wild females carrying satellite transmitters as part of a tagging program (under license from the State Committee for Nature Conservation of the Republic of Uzbekistan; see Burnside et al 2017), GPS location data (accuracy 618 m) were inspected daily; if a female had !2 repeat fixes from the same location, the area was visited to confirm the presence of a nest.…”
Section: Nest Searches and Monitoringmentioning
confidence: 99%
“…If a nest was not found after~30 min the tracking was stopped, to avoid keeping a female off her nest too long (data from nest cameras indicated that females take incubation breaks of~30 min; R. J. Burnside personal observation). For 27 wild females carrying satellite transmitters as part of a tagging program (under license from the State Committee for Nature Conservation of the Republic of Uzbekistan; see Burnside et al 2017), GPS location data (accuracy 618 m) were inspected daily; if a female had !2 repeat fixes from the same location, the area was visited to confirm the presence of a nest.…”
Section: Nest Searches and Monitoringmentioning
confidence: 99%
“…Studies on stopover ecology of bustards are scarce and limited to a few long-distance bustard species/populations, such the Asian Houbara Bustard Chlamydotis macqueenii (e.g. Combreau et al 1999, Tourenq et al 2004, Burnside et al 2017) and the Asian Great Bustard Otis tarda dybowskii (Kessler et al 2013). The stopover ecology of short-distance migratory bustards, such as the Iberian Little Bustard population, is completely unknown.…”
mentioning
confidence: 99%
“…Several aspects of this population (e.g. breeding productivity, habitat selection, migration and survival) have already been investigated (Koshkin et al 2014;Burnside et al 2016;Koshkin et al 2016a;Koshkin et al 2016b;Burnside et al 2017Burnside et al , 2018Guilherme et al 2018). Fieldwork was conducted annually during the entire breeding season (March-July) from 2012 to 2018 inclusive, with a satellite-tagging and brood-monitoring programme from 2013.…”
Section: Study Area and Populationmentioning
confidence: 99%
“…Backpack-mounted satellite transmitters have been deployed on a wide range of bustard Otididae species including African houbara Chlamydotis undulata (Hardouin et al 2015), Asian houbara C. macqueenii (Combreau et al 2011;Madon and Hingrat 2014;Burnside et al 2017;Dolman et al 2018), little bustard Tetrax tetrax (Marcelino et al 2018), great Indian bustard Ardeotis nigriceps (Habib et al 2016), kori bustard A. kori (Mmassy et al 2018), great bustard Otis tarda (Watzke 2007;Kessler et al 2013), Bengal florican Houbaropsis bengalensis (Mahood et al 2016;Jha et al 2018) and Ludwig's bustard Neotis ludwigii (Shaw et al 2014). These species fit a number of the criteria highlighted by Bodey et al (2018) as increasing risks of negative effects from backpack-mounted transmitters: all have flapping flight, many are migratory and for most the transmitters exceed 1% of body mass.…”
Section: Introductionmentioning
confidence: 99%